The use of BDA strategy in extensive reading improves students' learning achievement - Elfrida BR. Silalahi; Bertha Resivia Gayatri; Emmanuel Kyei (Universitas Muhammadiyah Malang, 2025)
Although there is empirical support for the Before-During-After (BDA) strategy, there is still a gap in its application in extensive reading programs, particularly in the context of English as a Foreign Language (EFL). This study investigates the effectiveness of the Before-During-After (BDA) strategy in enhancing English as a Foreign Language (EFL) students' reading comprehension in an extensive reading context. A quasi-experimental design with pretest-posttest control groups was used, involving 15 students in the experimental group and 23 in the control group at Merdeka University of Malang, Indonesia. The study assesses how BDA's structured phases (pre-, during-, post-reading) address common reading barriers such as idea identification, vocabulary deficits, and text structure analysis. The experimental group, which utilized the BDA strategy over 8 weeks, showed significant improvement in reading proficiency, with a mean post-test score increase of 22.3% compared to the control group's 15.2%. Statistical analysis confirmed the effectiveness of BDA (p<0.001). Qualitative data from student journals revealed that BDA activities such as vocabulary activation, predictive engagement, and visual literacy significantly aided comprehension. These findings underscore the value of BDA in overcoming specific EFL challenges, making it a practical tool for enhancing reading achievement in diverse educational settings. This implies that educators and curriculum developers should consider incorporating BDA-based strategies into EFL reading programs to support more effective and learner-centered literacy instruction.